Jorge Luis Borges e Peter Eisenman, Narrativa e Arquitetura - Passaro, Andrés Martin (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1995)
This study intends to make a comparison between the works of the w riter Jorge Luis Borges and of the architect Peter Eisenman. For this purpouse, there were selected "La casa de Asterión" a tale from Borges' book " El Aleph" and the "Guardiola House" a Peter Eisenman's project. The purpose is to look for an analogy between these tw o works. This idea came out from reading the criticals about Eisenman's works, which pointed out that some similiraty between the architect's thoughts and the w riter one's could be noticed. La casa de Asterion was chosen after passing through many "labyrinthic and abyssals'" texts (as stated Otilia Arantes)